BCL-2 dependence is a favorable predictive marker of response to therapy for chronic lymphocytic leukemia - Chong, Stephen Jun Fei; Lu, Junyan; Valentin, Rebecca; Lehmberg, Timothy Z.; Eu, Jie Qing; Wang, Jing; Zhu, Fen; Kong, Li Ren; Fernandes, Stacey M.; Zhang, Jeremy; Herbaux, Charles; Goh, Boon Cher; et al. (Molecular cancer, 2025)
Established genetic biomarkers in chronic lymphocytic leukemia (CLL) have been useful in predicting response to chemoimmunotherapy but are less predictive of response to targeted therapies. With several such targeted therapies now approved for CLL, identifying novel, non-genetic predictive biomarkers of response may help to select the optimal therapy for individual patients.
Gesehen am 31.07.2025